Teachers' Perspectives on Cyberbullying: A Cross-Cultural Study - Castellanos Sánchez, Almudena; Ortega-Ruipérez, Beatriz; Aparisi, David (International journal of environmental research and public health, 2022)
The aim of this work is to analyze the perceptions of Colombian, Spanish, and Ecuadorian teachers regarding cyberbullying from a cross-cultural perspective. A descriptive and analytical method was used with a quantitative approach and 240 teachers answered an ad hoc questionnaire. Most teachers in the three countries say that they do not know how to deal with this type of bullying and have not received training in this respect, with the percentages in the three countries being very similar. Spanish teachers have the highest percentage of lack of concern about cyberbullying and Colombian teachers are the ones who admit to having had the most cases of cyberbullying. In terms of reaction, the majority acted, but among those who did not, Ecuadorian teachers did not due to lack of knowledge. Forced by the pandemic to teach their classes online, teachers are increasingly concerned about cyberbullying. For the three countries, it is considered necessary to take measures in terms of legislating specific protocols to deal with cyberbullying at school and that the training plans for the degrees that give access to this profession include the competencies that allow teachers to develop appropriate strategies to respond to cyberbullying.
Keywords: cyberbullying; school bullying; perceptions; teaching skills; cross-cultural study; JCR; Scopus